A survey on students' perception of learning literature in the ESL classroom - Regina, Stewart Thiam (Universiti Malaysia Sarawak, (UNIMAS), 2005)
This study sought to find out learners' perceptions of learning literature in the ESL classroom. The study aimed to provide teachers a better understanding of the current situation of literature lesson. It also aimed to provide information regarding the material selections on the learners' preferred literary texts, learners' level of linguistic competency and learners' interest in learning literature. 40-item questionnaires were administered to a group of 60 Form Four students in the Sarikei District who made up the samples of the study. An additional instrument used in this study was the interview sessions. The results showed that there were both positive and negative findings regarding the students' perception of learning Literature in ESL classroom. Thus, by seeing through the eyes of learners, teachers can develop appropriate teaching materials and choose suitable literary texts that suit the needs of their learners.